Strand 2: Innovative Delivery: Methods and Approaches - Banks, Sheena; McConnell, David; Graebner, Celia (Proceedings of the International Conference on Networked Learning, 1998)
In this strand of the Conference Proceedings the papers address several themes concerned with the delivery of networked learning and the methods, approaches, cools and infrastructures used in that delivery.